Burnout of Greek Teachers: Measurement Invariance and Differences across Individual Characteristics - Angelos Gkontelos; Julie Vaiopoulou; Dimitrios Stamovlasis (European Journal of Investigation in Health, Psychology and Education, 2023)
Burnout (BT) is a vital determinant of work effectiveness and a well-studied psychological construct. The dominant theoretical perspectives have defined BT via the proposed dimensional structures and have provided the corresponding instruments for measuring them. The present endeavor adopts the Oldenburg Burnout Inventory (OLBI), as its purpose is to examine the psychometric properties of a short version for the Greek teachers and to find differences across their individual characteristics. The Greek short version of OLBI comprises two dimensions: Disengagement (four items) and Exhaustion (five items), with reliability measures utilizing Cronbach’s alpha and McDonald’s omega: Exhaustion (α = 0.810/ω = 0.823) and Disengagement (α = 0.742/ω = 0.756). Confirmatory factor analysis showed an adequate fit of the measurement model: χ2 = 320.291, df = 26, p < 0.001; CFI = 0.970; TLI = 0.958; RMSEA = 0.068; 90% CI of RMSEA = [0.062; 0.075]; SRMR = 0.067; NFI = 0.967; GFI = 0.986]. The proposed model is extracted after two studies (N1 = 134, N2 = 2437). The novel aspect of this endeavor is the measurement invariance explored across selected demographic variables. The findings supporting the measurement invariance make an essential contribution to the field, and the implications for educational research are provided along with a concise presentation of theoretical issues.